Living with chronic depression: reconstructing biographies and representations about their own illness - Alves, Fátima (2020)
The rise of chronic diseases, including chronic mental illness, as well as the changes in the social answers to mental illness require the assessment of their impact on the daily lives of individuals, groups and social organisations, but also require the understanding of the experiences, the changes and the adjustments at the level of identity and the ways of life of people with major depression diagnosis. In Portugal, there are few studies about the experience with mental illness, particularly on those that live with it in their daily lives. In this chapter, based on empirical evidence resulting from an exploratory study, we analyse the data from in-depth interviews with ten people with a psychiatric diagnosis of chronic depression, exploring the conceptions about their own illness and the perception of its impact on their daily life, seeking their personal experience and the senses they give to it. We sought to understand how people with major depression experience, understand, explain and interpret this condition, and cope with its consequences and impacts on the various levels and contexts where their life unfolds. Finally, we give special emphasis to their concepts and representations of their own illness.